Sports supplements user profile based on demographic, sports, and psychological variables: A cross-sectional study - Mera-Zouain, L.; Carballo, J. L.; Mora, M. C. (Nutrients, 2022)
Despite the high prevalence of sports supplement (SS) use, efforts to profile users have not been conclusive. Studies report that 30-95% of recreational exercisers and elite athletes use SS. Research found has mostly focused on demographic and sports variables to profile SS users, but little research has studied the psychological factors that may influence the use of SS. The purpose of this investigation was to classify, describe, and differentiate the profile of users and non-users of SS, considering demographic, sports, and psychological variables. A total of 554 participants completed the questionnaire. Overall, 45% of recreational exercisers and elite athletes reported using supplements. There were significant differences found regarding the use of SS between men and women (51% vs. 49%, p = 0.002; OR = 1.799), and when training 4 or more days per week (p = 0.001; OR = 1.526). Findings regarding the psychological variables have been found in the Adonis Complex. These results indicate that participants with greater concerns regarding physical appearance, tend to be SS users (p = 0.001; OR = 1.200). The results of this study fill a gap in previous research, and provide an approximate profile, including demographic, sports, and psychological variables of SS users.